Entrepreneurial training: a systematic review of the literature (2010-2020) - Costa, Evanilde Silva da; Ribeiro, Maria Edilene da Silva; Guimarães, André Rodrigues (Argumentum, 2022)
This text deals with entrepreneurial training in Brazilian higher education. The study builds an overview of academic output on entrepreneurial training in Brazilian higher education for the period 2010-2020. The methodology is a Systematic Literature review, in which relevant evidence on the subject was located, selected, evaluated, analyzed, and synthesized to categorize its objectives and results, and it discusses the main findings of the matrix of final categories. Content Analysis technique was employed for interpretation of the data. In the results, the five most frequent final categories in the works stand out: Entrepreneurial Characteristics (f = 96); Teaching-Learning Methodology (f = 86); Entrepreneurial Training (f = 56); Encouraging Entrepreneurship (f = 44) and Higher Education Institution (f = 30).